Análisis de la ejecución presupuestal de los ingresos y egresos de la empresa Electro Oriente S.A., periodo 2016 - 2020 - Rios Rengifo, Lorena Eugenia (2022)
Budget execution is a process by which the entity permanently controls and supervises the inflows and outflows of public resources that are generated by its nature, having as a measurement parameter, all those activities that have been programmed and projected. For its execution in a certain period, in such a way, it is possible to measure the management capacity. The present investigation entitled "Analysis of the budget execution of the income and expenses of the company Electro Oriente SA, period 2016 – 2020”, aims to determine the level of execution that said budget presents with respect to the study period. Likewise, the research was of a quantitative type and a non-experimental descriptive design – cross-sectional. From the analysis and discussion of the results that were obtained, it was possible to determine the budget execution of the income and expenses presenting a high level of execution in the study period.